A Preliminary Study of Parasitic Infections of Some Fishes from Kinabatangan River, Sandakan, Sabah - Hairul Hafiz Mahsol; Norizzah Zainuddin; Noor Farniza Habib Abdullah; Abdul Hamid Ahmad (Universiti Malaysia Sabah, 2014)
A survey of fishes of the Kinabatangan River was conducted to determine the fish types, abundance and prevalence of parasitic infection. The fishes were collected with gill nets in two distinct areas, named Abai and Bilit. Eleven fish species in ten genera and ten families were encountered. The family Ariidae formed 36.3% of the total number of individuals (n=80) while the rest were Pangasiidae (15%), Siluridae (11.3%), Cyprinidae (10%), Engraulidae (7.5%), Bagridae (6.3%), Toxotidae (6.3%), Sciaenidae (3.8%), Megalopidae (2.5%) and Clariidae (1.3%). Both ectoparasites and endoparasites especially intestinal helminth were recorded. The ectoparasite infestation rate was 45% whereas the endoparasite remain only 17.5%. The overall parasitic infection rate was more than half of sample (53.8%).This preliminary data indicated that almost half of the population of fishes from these areas could be exposed to parasitic infection.